Field‐size correction factors of a radiophotoluminescent glass dosimeter for small‐field and intensity‐modulated radiation therapy beams. Issue 1 (5th December 2017) - Hashimoto, Shimpei; Fujita, Yukio; Katayose, Tetsurou; Mizuno, Hideyuki; Saitoh, Hidetoshi; Karasawa, Katsuyuki
Abstract : Purpose: We evaluated the energy responses of a radiophotoluminescent glass dosimeter (RPLD) to variations in small‐field and intensity‐modulated radiation therapy (IMRT) conditions using experimental measurements and Monte Carlo simulation. Methods: Several sizes of the jaw and multileaf collimator fields and various plan‐class IMRT‐beam measurements were performed using the RPLD and an ionization chamber. The field‐size correction factor for the RPLD was determined for 6‐ and 10‐MV x rays. This correction factor, together with the perturbation factor, was also calculated using Monte Carlo simulation with the EGSnrc/egs_chamber user code. In addition, to evaluate the response of the RPLD to clinical‐class‐specific reference fields, the field‐size correction factor for the clinical IMRT plan was measured. Results: The calculated field‐size correction factor ranged from 1.007 to 0.981 (for 6‐MV x rays) and from 1.012 to 0.990 (for 10‐MV x rays) as the jaw‐field size ranged from 1 × 1 cm 2 to 20 × 20 cm 2 . The atomic composition perturbation factor for these jaw fields decreased by 3.2% and 1.9% for the 6‐ and 10‐MV fields, respectively. The density perturbation factor was unity for field sizes ranging from 3 × 3 cm 2 to 20 × 20 cm 2, whereas that for field sizes ranging from 3 × 3 cm 2 to 1 × 1 cm 2 decreased by 3.2% (for 6‐MV x rays) and 4.3% (for 10‐MV x rays). The volume‐averaging factor rapidly increased for field sizes below 1.6 × 1.6 cm 2 . The results for the MLC fields were similar to those for the jaw fields. For plan‐class IMRT beams, the field‐size correction and perturbation factors were almost unity. The difference between the doses measured using the RPLD and ionization chamber was within 1.2% for the clinical IMRT plan at the planning‐target volume (PTV) region. Conclusions: For small fields of size 1.6 × 1.6 cm 2 or less, it was clarified that the volume averaging and density perturbation were the dominant effects responsible for the variation in the RPLD response. Moreover, perturbation correction is required when measuring a field size 1.0 × 1.0 cm 2 or less. Under the IMRT conditions, the difference in the responses of the RPLD between the reference conditions and the PTV region calculated by Monte Carlo simulation did not exceed 0.8%. These results indicate that it is feasible to measure IMRT dosage using an RPLD at the PTV region.